2021
DOI: 10.1029/2021ja029904
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ICON/MIGHTI and TIMED/TIDI Neutral Wind Measurements in the Lower Thermosphere

Abstract: The Earth's upper atmosphere is a dynamic environment and neutral winds are a critical component of it. Neutral winds control a large part of the dynamics within the coupled upper atmosphere and ionosphere system and thus plays an important role in determining the state of the ionosphere-thermosphere (I-T) system at all latitudes. Due to the geometry of the Earth's geomagnetic field, neutral winds at lower latitudes can generate electric fields via the dynamo effect and push the ionospheric plasma upward and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 53 publications
5
21
0
Order By: Relevance
“…Harding et al showed a strong correlation (r = 0.82) between ICON-MIGHTI and specular meteor radars for coincident wind measurements with an average error of 4.5 m/s [19]. The agreement of MIGHTI/ICON and TIMED/TIDI atmospheric wind measurements in the MLT region has also been shown in Dhadly et al [14]. However, no study has yet considered the consistency of meteor radar and MIGHTI/ICON measurements of neutral wind in the MLT region on the basis of a full year of detection data.…”
Section: Introductionmentioning
confidence: 67%
See 4 more Smart Citations
“…Harding et al showed a strong correlation (r = 0.82) between ICON-MIGHTI and specular meteor radars for coincident wind measurements with an average error of 4.5 m/s [19]. The agreement of MIGHTI/ICON and TIMED/TIDI atmospheric wind measurements in the MLT region has also been shown in Dhadly et al [14]. However, no study has yet considered the consistency of meteor radar and MIGHTI/ICON measurements of neutral wind in the MLT region on the basis of a full year of detection data.…”
Section: Introductionmentioning
confidence: 67%
“…Comparing the results shown above, it could be seen that the consistency of zonal wind measurements from MIGHTI/ICON and meteor radar is better than that of meridional wind measurements, which may be caused by the orbit configuration of the ICON satellite [14]. The measurement of meridional wind from MIGHTI/ICON is naturally less accurate than that of zonal wind due to the north-south motion of the ICON satellite around Wuhan.…”
Section: Statistical Studymentioning
confidence: 79%
See 3 more Smart Citations